2008
DOI: 10.1375/twin.11.6.603
|View full text |Cite
|
Sign up to set email alerts
|

Linkage and Association Analyses of Longitudinally Measured Lipid Phenotypes in Adolescence

Abstract: The genetic basis of cardiovascular disease (CVD) is complex and still largely elusive. Plasma lipid concentrations are well-established risk factors for cardiovascular disease (CVD), and have adult heritabilities ranging from 0.48 to 0.87. Estimates for adolescents are slightly higher (range 0.71 to 0.82). To identify loci affecting lipid concentrations across adolescence, we analyzed longitudinal lipid data in a sample of 134 monozygotic and 626 dizygotic twin pairs at ages twelve, fourteen and sixteen, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Another locus near the KCNK9 gene on chromosome 8q24 also showed suggestive association with HMW adiponectin levels. Of note, in a previous genome-wide scan this locus was related to the levels of triglycerides (22). SNPs in genes ARL15 (rs4311394) and CDH13 (rs3865188 and rs7195409) were recently associated with total or HMW adiponectin levels (11,12,14).…”
Section: Discussionmentioning
confidence: 91%
“…Another locus near the KCNK9 gene on chromosome 8q24 also showed suggestive association with HMW adiponectin levels. Of note, in a previous genome-wide scan this locus was related to the levels of triglycerides (22). SNPs in genes ARL15 (rs4311394) and CDH13 (rs3865188 and rs7195409) were recently associated with total or HMW adiponectin levels (11,12,14).…”
Section: Discussionmentioning
confidence: 91%
“…A GWAS conducted by Middelberg RP et al ( 18 ) for plasma cholesterol found genes LPL, LIPC, CETP associated with HDL-C level and CELSR2, APOB, TOMM40 with LDL-C level. Another two GWAS studies identified SRGAP2, HOXC13 and CD47, DUSP4 that were associated with HDL-C and TC level, respectively ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it should be noted that the chromosomal region, 6p25.3 to 6p24.3, has already been associated with TG levels (Middelberg et al, 2008), total body fat mass in females (Lei et al, 2009) and neuroendocrine carcinomas of uterus and ovary (Aboura et al, 2009;Mhawech-Fauceglia et al, 2008). The genetic variants we investigated -like another important polymorphism in the F13A1 gene (rs5985, Val34Leu) -might also have effects on cell specific expression, stability or availability as well as activity of the protein (Muszbek et al, 2008).…”
Section: Discussionmentioning
confidence: 95%